Innovate, Inform, And Inspire: Jazz Up Medical Communication at the 2024 Medical Writing & Communication Conference: October 23-26, New Orleans - Sequeira, Michele (AMWA Journal, 2024)
It's almost here! Get ready for the AMWA 2024 Medical Writing & Communication Conference in the Big Easy. This year’s conference is scheduled for October 23 through October 26 at the New Orleans Marriott hotel. Register now for the conference at the Annual Conference website (https://site.pheedloop.com/event/AMWA2024/home/).